Effects of Hedging against Risk management Strategy on Supply Chain performance - Mburu, David Kiarie; Ngugi, Dr. Patrick Karanja; Ogollah, Dr. Kennedy (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
In an organization today the importance of supply chain performance support for successfulorganization strategy implementation has for a long time been recognized in the SCM literature but the management of risks as a result of interruptions has not received adequate attention (Cooper, 2003; Magnan & Christopher, 2005). Chopra and Sodhi (2004) identify the wider consequences of a failure to manage risks effectively. These include not just only financial losses but also reduction in product quality, damage to property and equipment, loss of reputation in the eyes of customers, suppliers and the wider public, and delivery delays. There is also evidencethat economic, political and social developments over the past decade appear to be increasing the risk of supply chain disruptions as supply chains are getting longer and more complex and areinvolving more partners due to the increase in global sourcing (Hendricks & Singhal, 2005).A perfect Supply chain environment encourages fierce competition among suppliers, often requiring playing one supplier against the others, and uses rewards or punishment based on performance. In this environment partners are interchangeable and under the discipline of a free market, promote a healthy and vigorous supply base determining the performance of supply chains in most organizations (Brau, 2005). Lewis (2003) notes that, the essence of supply chain management is as a strategic weapon to develop a sustainable competitive advantage by reducing investment without sacrificing customer satisfaction. Since each level of the supply chain focuses on a compatible set of objectives, redundant activities and duplicated effort can be reduced. In addition, supply chain partners openly share information that facilitates their ability to jointly meet end-user’s needs bringing adequate change to its performance (Lewis, 2003). While reduced cost is typically a result, supply chain performance should emphasize leveragingthe skills, expertise, and capabilities of the firms who comprise this competitive network referred to. The importance of getting close to key customers and thus a sustainable supply chain riskmanagement strategy extends these linkages upstream and down (Cooper, 2003). Supply chain risk strategy development should be part of the business unit planning process which includes efforts aimed at developing and maintaining global information systems, addressing strategic aspects of make-or-buy issues, and accessing and managing innovation with the purpose of protecting and enhancing core technologies (Peck, 2005). Developing a supply chain strategy is based on understanding the elements of sourcing strategy, information flows (internal and external), new product co-ordination, concurrent procurement, teaming arrangements, ommodity/component strategies, long-term requirements planning, industry collaboration, and staff development (Magnan, 2005). Supply chain management is built on a foundation of trust and commitment (Rice & Canioato, 2003). The consensus is that trust can contribute significantly to the long-term stability of an organization (Slack, 2011). Commitment is the belief that the trading partners are willing todevote energy to sustaining this relationship (Smith, 2004). Hence, through commitment partners dedicate resources to sustain and further the goals of the supply chain and to a large degree,commitment “ups the ante” and makes it more difficult for partners to act in ways that mightadversely affect overall supply chain performance (Slack, 2011). Trading partners supply chain become integrated into their major customers’ processes and more tied to their overarching goals. For instance, in most business transactions, supply chain partners willingly share information about future plans and designs, competitive forces, and R&D. Partnersrecognize that their long-term success is as strong as their weakest supply chain partner(Abdallah & Moneim, 2004).